1996
DOI: 10.2355/isijinternational.36.968
|View full text |Cite
|
Sign up to set email alerts
|

High Nitrogen Steels. Influence of Shielding Gas Composition and Welding Parameters on the N-content and Corrosion Properties of Welds in N-alloyed Stainless Steel Grades.

Abstract: TIG welding using different heat inputs, arc lengths and shielding gas nitrogen contents was performed, The aim was to evaluate the possibilities to avoid nitrogen losses on welding or even increase the weld metal nitrogen content and thereby improve the corrosion properties and, in the case of duplex grades, also to improve the phase balance, Three different nitrogen-alloyed duplex grades and one superaustenitic grade were investigated, Thecorrosion resistance in terms of CPT, Critical Pitting Temperature, of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 0 publications
1
26
0
7
Order By: Relevance
“…16) A value of k 1 ϭ10 gave a good fit to the experimental results. Support for this value was also given by Bandopadhyay et al and Hertzman et al 27,31) The nitriding capacity of the plasma is thus about ten times larger than a molecular gas of the same composition.…”
Section: Calculation Of Mass Transfer and Plasma Nitriding Coefficientssupporting
confidence: 48%
See 1 more Smart Citation
“…16) A value of k 1 ϭ10 gave a good fit to the experimental results. Support for this value was also given by Bandopadhyay et al and Hertzman et al 27,31) The nitriding capacity of the plasma is thus about ten times larger than a molecular gas of the same composition.…”
Section: Calculation Of Mass Transfer and Plasma Nitriding Coefficientssupporting
confidence: 48%
“…Kokawa. 31) Cross et al 32) found that 250 ppm contamination of oxygen in the shielding gas increased significantly the weld metal nitrogen content in welding of duplex stainless steels under hyperbarric conditions. Hertzman and Wessman 33) investigated plates from five stainless steels including the duplex 2205 the super duplex SAF 2507 and the super austenitic 654 SMO.…”
Section: Nitrogen Balance In Stainless Steel Tig Weldsmentioning
confidence: 99%
“…19,20) The nitrogen flux between the weld pool and plasma is determined by the activity difference between them, and the direction of the nitrogen flux will be towards regions with lower nitrogen activity. 8,21) The nitrogen activity of the plasma is mainly determined by the nitrogen partial pressure in the plasma in this case, which is related to the nitrogen content in the shielding gas. The nitrogen activity of the plasma increases with the increase of the nitrogen content in the shielding gas.…”
Section: Nitrogen Contentmentioning
confidence: 99%
“…Some problems will probably occur in welding of HNS, such as nitrogen loss, nitride, hot cracking and so on. [7][8][9][10][11][12] The nitrogen loss in the weld metal consists of the nitrogen desorption and nitrogen pore. Because high properties are attributed to high nitrogen content, the nitrogen loss in the weld metal will result in the decrease of mechanical properties during welding of HNS.…”
Section: Introductionmentioning
confidence: 99%
“…Οι αυξθμζνεσ τιμζσ ολκιμότθτασ δίνουν τθ δυνατότθτα μεγάλθσ ψυχρισ παραμόρφωςθσ *20+, ενϊ ςτισ ιδιότθτζσ τουσ πρζπει να προςτεκεί και θ πολφ καλι ςυγκολλθςιμότθτα, ιδιότθτα απαραίτθτθ ςχεδόν ςε όλεσ τισ εφαρμογζσ ενόσ μοντζρνου υλικοφ [21][22][23][24][25]. Κφρια κραματικά ςτοιχεία των υπερωςτενιτικϊν χαλφβων, εκτόσ των αυξθμζνων ποςοςτϊν χρωμίου και νικελίου, είναι το μολυβδαίνιο και το άηωτο, ενϊ διατθρείται πολφ χαμθλά το ποςοςτό του άνκρακα.…”
Section: εισαγωγηunclassified